Comparative Analysis of Students Learning Achievement in The Advanced Public Sector Accounting - Suharyono, Suharyomo; Mule, Yurika Ariati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
Based on semester credit units (SKS) students must be able to complete public sector accounting subjects correctly in accordance with the provisions. This study was conducted to determine whether there is a difference in understanding the learning outcomes of advanced public sector accounting courses between classes A and B. To test the analysis using the Mann-Whitney nonparametric test. The population in this study were 52 4th semester students in the D4 Accounting Public Accounting Study Program. The results of this study indicate that learning understanding or the ability of students in advanced public sector accounting courses between class A and class B are different. Differences in the learning environment in advanced public sector accounting courses in each class affect student learning outcomes